Simulation of Photon Correlation Spectroscopy Signal Using Orthogonal Inverse Wavelet Transform - WANG Yajing; DOU Zhenhai (Institute of Advanced Engineering and Science, 2013)
Computer simulation is a more convenient and faster method obtaining photon correlation spectroscopy (PCS) signal. Based on orthogonal inverse wavelet transform (OIWT), a new simulation method is developed. This method considers that PCS signal of a single scale is composed of several sub-band signals with different characteristic. According to the relationship of power spectrum of PCS signal and orthogonal wavelet coefficients of every scale, using OIWT, PCS signal can be obtained by simulation of several different sub-band signals. Using this method, PCS signals of 90nm, 600nm and1000nm are respectively simulated. Mean square errors of the power spectrums of the simulation signals and their theoretical power spectrums are e-5 order of magnitude. The relative errors of particle size inverted from simulation signals are less than 2.47%. Comparison of simulation and experiment proves that that OIWT is feasible for simulation of PCS signal. In addition, by analyzing the influence of simulation parameters on simulation accuracy, we get relationship of particle size, decomposition scale and sampling frequency. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3487